2020
DOI: 10.7150/ijms.47076
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of three classification systems of Prepregnancy Body Mass Index with Perinatal Outcomes in Japanese Obese Pregnant Women: A retrospective study at a single center

Abstract: In Japan, pregnant women are diagnosed as obese if the prepregnancy body mass index (BMI) is ≥25 kg/m 2. However, this is different from other countries. The Institute of Medicine (IOM) classifies prepregnancy BMI as underweight (BMI <18.5 kg/m 2), normal weight (BMI 18.5-24.9 kg/m 2), overweight (BMI 25.0-29.9 kg/m 2), and obese (BMI ≥30 kg/m 2). In addition to these four categories, the American College of Obstetricians and Gynecologists (ACOG) classifies prepregnancy BMI as obesity class I (BMI 30.0-34.9 kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…A multicenter Chinese retrospective study showed that overweight and obesity were a risk factor for HDP ( 37 ). Another Japanese study obtained a similar result that obese pregnant women were significantly associated with an increased risk of HDP ( 38 ). Current theory believes that obesity is a chronic inflammation and accumulating studies have found abnormal immune cells and cytokines in pregnant women with obesity such as CD4 + T cells, macrophages, IL-6, and TNF-α ( 39 42 ).…”
Section: Discussionmentioning
confidence: 66%
“…A multicenter Chinese retrospective study showed that overweight and obesity were a risk factor for HDP ( 37 ). Another Japanese study obtained a similar result that obese pregnant women were significantly associated with an increased risk of HDP ( 38 ). Current theory believes that obesity is a chronic inflammation and accumulating studies have found abnormal immune cells and cytokines in pregnant women with obesity such as CD4 + T cells, macrophages, IL-6, and TNF-α ( 39 42 ).…”
Section: Discussionmentioning
confidence: 66%
“… 14 The standard WHO BMI classifications from previous studies were applied to this study. 15 , 16 Furthermore, it is critical to comprehend how lifestyle choices affect both underweight and overweight/obesity, affecting their respective burdens. Hence, this study focuses on women's health with changes in lifestyles at young and middle age and its effect on BMI.…”
Section: Introductionmentioning
confidence: 99%